Bibliometric Analysis: The Development of Research and Publications on Sustainable Development Goals (SDGs) and Their Impact on Investment - Maulidia, Nuke (International Journal of Economics (IJEC), 2025)
Purpose: This study aims to analyse literature related to Sustainable Development Goals (SDGs) and their impact on investment using bibliometric analysis. Design/Methodology/Approach: The study utilises 41 articles related to SDGs and investment collected from the Scopus database. The bibliometric analysis includes keyword analysis, trend analysis, and density visualisation. Findings: The research results indicate four main topic clusters: 1) carbon dioxide, climate change, economic development, etc.; 2) foreign direct investment, governance, private sector, etc.; 3) economic and social effects, emerging economies, environmental quality, etc.; 4) alternative energy, environmental economics, spatiotemporal analysis. The topics of "Sustainable Development Goal" and "investment" are the main focus in the literature. Practical Implications: Bibliometric analysis can help researchers understand the development of trends and main topics in the field of research related to SDGs and investment. These findings can be used to develop more coordinated and directed research programs in the future.